PROMOTING SUSTAINABILITY IN UNDERGRADUATE PROGRAM: STUDENTS’ PERCEPTION IN GREEN CHEMISTRY COURSE - Listyarini, Risnita Vicky (International Journal of Indonesian Education and Teaching (IJIET), 2019)
Global challenges such as climate change, decreasing natural resource and environmental pollution become major threats to global society now. Transformation toward sustainability should be promoted in practices. Universities and higher education (HE) plays an essential role in shaping the individual way of thinking and acting to become sustainability change-maker. This research aimed to study about students’ perception towards implementation of Green Chemistry Course in undergraduate program of Chemistry Education Study Program, Sanata Dharma University. Through the implementation of green chemistry course, it is expected to promote sustainability to prospective teachers. Findings from this research indicated positive perception towards Green Chemistry Course in terms of students’ awareness of environmental issues and implementation of principles of green chemistry in life.DOI: doi.org/10.24071/ijiet.2019.030107